A power quality evaluation method for distribution system with renewable energy. Issue 5 (3rd May 2020) - Chen, Jinxin; Pan, Guobing; Ouyang, Jing; Zhang, Libin
ABSTRACT: Power quality evaluation data are heterogeneous and fluctuating, and there are large subjective factors in the evaluation process. To solve this problem, a power quality evaluation method based on incentive punishment factor and the ordered weighted aggregation (OWA) operators was proposed. The integrity and fairness of the evaluation information were guaranteed, through the homogenisation of the evaluation data. And using incentive and penalty factors to calculate the single index evaluation value without considering the time factor. By introducing the time weights and adopting the linear target programming model and ordered the weighted averaging operator to get the primary evaluation values of the indices in the inspection period. Then, the minimum variance method was used to get index weights, and the ordered weighted geometric averaging (OWGA) operator was applied to obtain the comprehensive evaluation value of the power quality. Finally, the power quality of a distribution system with photovoltaic generation under different load conditions is analysed as an example. The results showed that the method proposed in this paper distinguishes the power quality level under various load conditions significantly, which verify the feasibility and effectiveness of the model.